THE LEVEL OF FOOTBALL ANALYSIS ON THE OPTIMAL DEVELOPMENT PERIOD OF THE GOLDEN AGE (DYSMENORRHEA) OF ADOLESCENTS AGED 13 TO 17 YEARS - Adelia Utama Bastian; Reza Adhi Nugroho (RADJA PUBLIKA, 2025)
Football is one of the sports that can support physical, mental, and social development, especially during the optimal development period (golden age) of adolescents. This period, which occurs at the age of 13-17 years, is an important period in physical development and motor skills. This study aims to analyze the effect of football on the optimal development of female adolescents in this age range. The study used a cross-sectional method involving 60 female adolescents who actively participated in football training at a football school in Central Java. The data collected included physical development (height, weight, and nutritional status based on BMI/age), motor development (balance, agility, and muscle strength), and social development (team interaction and self-confidence). The results showed that participation in football had a significant effect on physical development (p<0.05), motor (p<0.01), and social (p<0.01). This study concluded that football provides positive benefits during the optimal development period of female adolescents, especially in the physical, motor, and social aspects. Longitudinal studies with a larger population coverage are needed to identify appropriate training strategies to maximize development without increasing the risk of injury. Future research could explore the specific mechanisms through which football training influences these developmental aspects in female adolescents. It would be valuable to investigate whether the observed benefits are unique to football or if similar effects could be achieved through other team sports. Additionally, examining the long-term impact of sustained football participation on female adolescents' overall health, academic performance, and career prospects could provide valuable insights for policymakers and educators.